INTERNATIONAL ISOTOPES MARKETS - S. Z. Zhiznin; V. M. Timohov (Vestnik MGIMO-Universiteta)
The paper studies world markets of stable and radioactive isotopes. Isotopes have found various applications in science, industry, agriculture and other sectors of the economy, but especially - in medicine. Nuclear medicine is developing intensively all over the world thanks to the success in the treatment of various diseases with the help of radioactive pharmaceuticals (radiopharmaceuticals). The article uses empirical data from a forecast study of the global radiopharmaceuticals market made in 2015 by a research company «Markets and Markets» for the European, North American and global markets. The paper also analyzes the statistical data on the global export and import of natural uranium, enriched and depleted uranium, plutonium, thorium and some stable isotopes of non-medical purposes, presented by a company «Trend economy» in 2014. Despite a unique industrial base for the production of isotopes created in the Soviet Union Russia occupies a modest position on the world market of nuclear medicine except for certain areas. More than 80% of isotopes, produced in USSR were consumed domestically, the export of the stable and radioactive isotopes was in equal proportions. Now the country's domestic radiopharmaceuticals market is poorly developed. To radically change the situation, it is necessary to carry out reforms that stimulate the development of nuclear medicine.